Typification of two newly recorded species of Ampelocissus (Vitaceae) for Thailand - Trias-Blasi, Anna; Watson, Mark F.; Chayamarit, Kongkanda; Parnell, John A.n. (Phytotaxa, 2015)
Two Ampelocissus species are newly recorded for Thailand: Ampelocissus araneosa (Dalz.) Planch. ex Gamble and Ampelocissus rugosa (Wall. ex Roxb.) Planch. Full typification is presented together with images of the type material, and descriptions and distribution maps of the species in Thailand. A key to all Thai Ampelocissus is included.